Association of New York Scientists 1947 newsletter - Association of New York Scientists (1947)
1947 newsletter for the Association of New York Scientists (ANYS). The newsletter discusses the association's purpose and goals. ANYS believed in international control of atomic energy and bacterial warfare, a national science foundation, and civilian control of the United States Atomic Energy Commission.
Keywords: Nuclear energy; Association of New York Scientists; Newsletters; U.S. Atomic Energy Commission